Climate change, the green economy and reimagining the city: the case of structurally disadvantaged European maritime port cities - Jonas, Andrew E.G.; Wurzel, Rüdiger K.W.; Monaghan, Elizabeth; Osthorst, Winfried (DIE ERDE – Journal of the Geographical Society of Berlin, 2017)
The concept of the New Environmental Politics of Urban Development (NEPUD) examines the impact of international and national environmental regulation on the politics of urban development. The NEPUD concept emerged from case studies of environmental governance in entrepreneurial cities. However, little is known about the concept’s relevance for less competitive cities, especially urban centres facing profound problems associated with economic decline, social deprivation and negative external images or ‘structurally disadvantaged cities.’ This paper examines how the NEPUD has played out within two structurally disadvantaged maritime port cities in Northern Europe, Hull (UK) and Bremerhaven (Germany). Both cities face serious social and economic challenges associated with long-term industrial decline, such as high unemployment rates, low skill levels, economic peripherality, and poor external images. Nevertheless, new opportunities opened up by climate change and the green economy have prompted political actors in Hull and Bremerhaven to build new alliances between local government, business and civil society and enhance governance capacities on climate change and green urban development. Highlighting similarities and differences between these two places, the paper reveals how climate change regulations provide opportunities for certain structurally disadvantaged cities to attract ‘green jobs’ and transform their external image.